2004
DOI: 10.1590/s0004-282x2004000200005
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disorders in pregnancy

Abstract: ABSTRACT:Context: The precise function of sleep in animals and human beings is still unknown, and any sort of physical, social or psychological variation may change the normal sleep-wake cycle. Purpose: This research aims is to determine the sleep disorders (SD) for each of the three trimesters of the pregnancy comparing them to the pre-pregnancy state (PG). Method: SD were investigated in three hundred pregnant women 11-to 40-years-old through with a brief clinical interview based on directed questions. One h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 14 publications
1
19
0
5
Order By: Relevance
“…Estes ajustes podem ser considerados um estado de saúde que envolve alterações fisiológicas iguais ou maiores do que as alterações de muitos estados patológicos 1,2 . Sendo assim, o organismo necessita de um tempo maior para a reposição energética, porém, este processo de reposição de energia é prejudicado por características típicas gestacionais, como por exemplo, o aumento da frequência urinária que também interfere no sono 3 .…”
Section: Qualidade De Vida Em Gestantes Com Alterações Do Sonounclassified
See 1 more Smart Citation
“…Estes ajustes podem ser considerados um estado de saúde que envolve alterações fisiológicas iguais ou maiores do que as alterações de muitos estados patológicos 1,2 . Sendo assim, o organismo necessita de um tempo maior para a reposição energética, porém, este processo de reposição de energia é prejudicado por características típicas gestacionais, como por exemplo, o aumento da frequência urinária que também interfere no sono 3 .…”
Section: Qualidade De Vida Em Gestantes Com Alterações Do Sonounclassified
“…A diminuição do tempo de sono pode gerar alterações no funcionamento físico, ocupacional, cognitivo, social, além do cansaço mental 4 . Mesmo com o repouso, o sono inadequado pode causar diminuição no desempenho no trabalho, irritabilidade, dificuldade na concentração, inquietação e diminuição na capacidade de suportar a dor 1,3 . As alterações relacionadas ao sono podem ser causadas pelas mudanças fisiológicas na gravidez, como desconforto no posicionamento durante o sono, síndrome das pernas inquietas e pesadelos, fazendo com que as gestantes reclamem da baixa qualidade de sono, menor duração do sono, despertar noturno, dificuldade em adormecer e menor eficiência do sono.…”
Section: Qualidade De Vida Em Gestantes Com Alterações Do Sonounclassified
“…In fact, pregnant women's sleep quality may be faced with some challenges due to the systematic changes caused by hormonal, psychological, emotional and physical factors that happen during pregnancy (Lopes et al, 2004). It is claimed that 79% of pregnant women are faced with the painful challenge of sleep deprivation (American Academy of Sleep Medicine, 2005), and the prevalence of sleep disorders has been reported by many researchers (Lee, 1998;Neau, Texier, & Ingrand, 2009;Okun, Wisniewski, & Wisner, 2013;Tsai, Lin, Kuo, & Thomas, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the Iranian studies have also reported that 87.2% of pregnant women encounter sleep quality problems ( Jahdi, Rezaei, Beboodi, & Hagani, 2013). Problems with the quality of sleep can result in increased anxiety over caring for babies or postpartum depression (Lee & Gay, 2004;Lopes et al, 2004). Additionally, this predicament can cause problems, including premature delivery and giving birth to underweight babies (Smith, Huang, & Manber, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…As desordens respiratórias do sono, mais prevalentes em gestantes com sobrepeso e obesas 10,21 , têm sido associadas a síndromes hipertensivas 21,22 , sintomas depressivos 23,24 , diabetes mellitus gestacional 25 e maior probabilidade de parto cesárea 26 , assim como desfechos perinatais adversos, como baixo peso ao nascer 17 , restrição do crescimento intrauterino 17 e admissão na UTI neonatal 26 . Apesar de existirem diversos estudos sobre as características do sono 10,12,18,21,27 e a obesidade durante a gestação 4,5,28 , há poucos estudos sobre a possível influência do sobrepeso na qualidade do sono durante a gestação 10,13,21,24 e não identificamos estudos nacionais sobre o tema.…”
unclassified